Enhancing client welfare through better communication of private mental health data between rural service providers - Burmeister, Oliver Kisalay; Islam, Md Zahidul; Dayhew, Miriam; Crichton, Merrilyn (Australasian Journal of Information Systems, 2015)
Client welfare is detrimentally affected by poor communication of data between rural service providers, which in part is complicated by privacy legislation. A study of service provision involving interviews with mental health professionals, found challenges in communicative processes between agencies were exacerbated by the heavy workloads. Dependence on individual interpretations of legislation, and on manual handling, led to delays that detrimentally affected client welfare. The main recommendation arising from this article is the creation of an ehealth system that is able to negotiate differing levels of access to client data through centralised controls, where the administration of that system ensures that it stays current with changing legislative requirements. The main contribution of the proposed model is to combine two well-known concepts: data integration and generalisation. People with mental illness are amongst the most vulnerable members of society, and current ehealth systems that provide access to medical records inadequately cater to their needs.